2020
DOI: 10.1002/acm2.13045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of magnetic field regulation in conjunction with the volumetric repainting technique on the spot positions and beam range in pencil beam scanning proton therapy

Abstract: Purpose The objective of this study was to evaluate the impact of the magnetic field regulation in conjunction with the volumetric repainting technique on the spot positions and range in pencil beam scanning proton therapy. Methods “Field regulation” — a feature to reduce the switching time between layers by applying a magnetic field setpoint (instead of a current setpoint) has been implemented on the proton beam delivery system at the Miami Cancer Institute. To investigate the impact of field regulation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…and "up" directions based on the findings by Rana et al, 23 although layer switching time could slightly vary from 1 s when plans are delivered on the machine. The simulated treatment delivery time for the cohort of patients in the current study showed the feasibility of delivering volumetric repainting plans mitigating the interplay effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…and "up" directions based on the findings by Rana et al, 23 although layer switching time could slightly vary from 1 s when plans are delivered on the machine. The simulated treatment delivery time for the cohort of patients in the current study showed the feasibility of delivering volumetric repainting plans mitigating the interplay effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the IBA ProteusPLUS machine, if the current regulation feature is employed, the energy layer switching time in the "up" direction can take up to 6 s. 23,24 Such a large energy switching time is not clinically acceptable. However, the use of magnetic field regulation feature on the IBA ProteusPLUS machine can reduce the energy layer switching time in the "up" direction from~6 s to~1.3 s. 23,24 Such a decrease in the energy layer switching time demonstrates the feasibility of delivering the volumetric repainting plan with an alternating order and improve the beam delivery efficiency. Another important point to note is that the current study was performed with an assumption of proton beam delivery using magnetic field regulation on the IBA ProteusPLUS machine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations